Digestive enzymes in the ontogenetic stages of the southern king crab, Lithodes santolla - Saborowski, R.; Thatje, S.; Calcagno, Javier Ángel; Lovrich, Gustavo Alejandro; Anger, K. (Marine Biology)
The early ontogenetic stages of the sub-Antarctic king crab Lithodes santolla were analyzed for the presence and activities of a set of important digestive enzymes. The eggs and non-feeding larvae (zoea I-III, megalopa) showed high activities of esterases, phosphatases, and exopeptidases indicating the enzymatic ability to utilize endogeneous yolk reserves. SDS-PAGE showed a continuous decrease of proteins or proteids in the range of 59-81 kDa during ontogenetic development from the eggs through the zoeal stages to the first juvenile crab stage, CI. This reduction reflects the degradation of storage compounds during lecithotrophic larval development. Activities of the endopeptidases, trypsin and chymotrypsin, were low in eggs and larvae but increased significantly in the first juvenile crab stage. These enzymes typically facilitate the first steps of proteolysis in the extra-cellular spaces of the midgut gland and in the stomach. Their scarcity indicates that the larvae of L. santolla are physiologically not prepared to digest external food. This ability seems to appear first in the CI stage. Extracts of juvenile midgut glands and the gastric fluids of adults showed high activities of a variety of digestive enzymes including phosphatases, carbohydrases, as well as endo- and exopeptidases. High activities of digestive enzymes in adults may compensate for scarce food supply and rate-limiting low temperatures in the predominantly sub-Antarctic habitats of L. santolla. Fil: Saborowski, R. Alfred-Wegener-Institut. Helmholtz-Zentrum für Polar und Meeresforschung; Alemania Fil: Thatje, S. Alfred-Wegener-Institut. Helmholtz-Zentrum für Polar und Meeresforschung; Alemania. University of Southampton; Reino Unido Fil: Calcagno, Javier Ángel. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Lovrich, Gustavo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones ...